Surgical site infection after breast cancer sur gery at 30 days and associated factors - Joana-Cristi; Jorge-Alberto; Wilmar-Arle; Jorge Madrid; Maria-Angelic; Rodrigo-Alberto A; Jesus Ochoa
Abstract Background: The incidence of surgical site infection (SSI) in breast surgery has been higher than expected, considering this is a clean surgical procedure. Few studies have reported an incidence of less than 5.0% and most publications report an incidence of between 10.2% and 30.0%. Objective: To estimate the incidence, associated factors and interval free from infection at 30 days postsurgery in women who underwent oncological and reconstructive breast surgery. Methods: Prospective cohort study of women with breast cancer who underwent conservative or radical breast surgery at a reference medical center in Medellín, Colombia. The outcomes were SSI and time to the event. The survival analysis of freedom from infection was performed using the Kaplan Meier method and the Cox proportional hazard model for multivariate analysis. Results: Of the 308 consecutive surgical breast oncology procedures performed, 161 (52.3%) were quadrantectomies and 147 (47.7%) were mastectomies, with an SSI incidence of 16.2% (50 cases). The associated risk factors were seroma-hematoma, which occurred in 79 (25.6%) cases, hazard ratio (HR) 2.7 (95% CI 1.5-4.9); and the presence of drainage devices, HR 5.6 (95% CI 2.2-14.3). The median time to the development of SSI was 16 days. Conclusion: Our study shows that the presence of postoperative seroma-hematoma and long-term drainage device use were independent risk factors for SSI in oncological breast surgery. (c) 2016 ACIN. Published by Elsevier Espana,˜ S.L.U. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).